Das Motiv des Labyrinths in Ulf Erikssons Xaviers hemlighet und Aris Fioretos‘ Stockholm noi - Berf, Poul (Folia Scandinavica Posnaniensia, 2007)
Since the days of the Minotaur in the labjrrinth of Knossos, the labyrinth is strongly connected with the concept of urbanity. In modem Uterature the labsrrinth has played a major role as a metaphor for the city and the forlomness of the individual in the big cities. Ulf Eriksson and Aris Fioretos, two contemporary Swedish noyelists, discuss in recent novels {Xaviers hemlighet and Stockholm noir) the relevance of the metaphor todey. For Eriksson the labyrinth is still apt metaphor for life in the big cities, whereas the protagonist in Fioretos' novel in the end rejects the concept in favour of a more subjective access to urban life.